2022
DOI: 10.1021/acs.iecr.2c01931
|View full text |Cite
|
Sign up to set email alerts
|

Friedel–Crafts Synthesis of Carbazole-Based Hierarchical Nanoporous Organic Polymers for Adsorption of Ethane, Carbon Dioxide, and Methane

Abstract: The Friedel–Crafts (FC) reaction is a prominent synthetic tool for rapidly constructing complex molecular frameworks, but syntheses of carbazole-based nanoporous organic polymers (CNOPs) via FC hydroxyalkylation are rare. Herein we report the acid-catalyzed FC hydroxyalkylation synthesis of two CNOP networks, prepared (using p-phthalaldehyde) from 1,3,5-tris­(9-carbazolyl)­benzene and tris­[4-(9H-carbazol-9-yl)­phenyl]­amine. The specific surface areas of the CNOPs ranged from 1374 to 1546 m2/g, and the CNOPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 57 publications
(113 reference statements)
2
18
1
Order By: Relevance
“…The BET specific surface area ( S BET ), microporous surface area, microporous volume, and total pore volume for CNOP-5 are 1425 m 2 ·g –1 , 1038 m 2 ·g –1 , 0.85 cm 3 ·g –1 , and 1.18 cm 3 ·g –1 , respectively. The value of S BET obtained for the CNOP-5 polymer exceeds or competes with those of other previously reported carbazole-based nanoporous organic polymers, such as PCNs (393–674 m 2 ·g –1 ), CTF-CAR (278 m 2 ·g –1 ), CNOPs (769–1546 m 2 ·g –1 ), , CSU-CPOPs (269–1032 m 2 ·g –1 ), Car-COFs (721–1334 m 2 ·g –1 ), CPOPs (510–1430 m 2 ·g –1 ), and other types of porous polymers. , Figure (b) illustrates the pore size distribution of CNOP-5 based on nonlocal density functional theory (NLDFT). As displayed in Figure (b), the CNOP-5 polymer has micropores centered at 0.97/1.37 nm and mesopores centered at 3.98 nm.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…The BET specific surface area ( S BET ), microporous surface area, microporous volume, and total pore volume for CNOP-5 are 1425 m 2 ·g –1 , 1038 m 2 ·g –1 , 0.85 cm 3 ·g –1 , and 1.18 cm 3 ·g –1 , respectively. The value of S BET obtained for the CNOP-5 polymer exceeds or competes with those of other previously reported carbazole-based nanoporous organic polymers, such as PCNs (393–674 m 2 ·g –1 ), CTF-CAR (278 m 2 ·g –1 ), CNOPs (769–1546 m 2 ·g –1 ), , CSU-CPOPs (269–1032 m 2 ·g –1 ), Car-COFs (721–1334 m 2 ·g –1 ), CPOPs (510–1430 m 2 ·g –1 ), and other types of porous polymers. , Figure (b) illustrates the pore size distribution of CNOP-5 based on nonlocal density functional theory (NLDFT). As displayed in Figure (b), the CNOP-5 polymer has micropores centered at 0.97/1.37 nm and mesopores centered at 3.98 nm.…”
supporting
confidence: 77%
“…The BET specific surface area (S BET ), microporous surface area, microporous volume, and total pore volume for CNOP-5 are 1425 m 2 •g −1 , 1038 m 2 • g −1 , 0.85 cm 3 •g −1 , and 1.18 cm 3 •g −1 , respectively. The value of S BET obtained for the CNOP-5 polymer exceeds or competes with those of other previously reported carbazole-based nanoporous organic polymers, such as PCNs (393−674 m 2 • g −1 ), 18 CTF-CAR (278 m 2 •g −1 ), 19 CNOPs (769−1546 m 2 • g −1 ), 2,17 CSU-CPOPs (269−1032 m 2 •g −1 ), 20 Car-COFs (721−1334 m 2 •g −1 ), 21 CPOPs (510−1430 m 2 •g −1 ), 22 and In addition, at both temperatures and pressures, the adsorption isotherms for CNOP-5 differ significantly, with gas uptakes uniformly decreasing in the order C 3 H 8 > C 2 H 6 > CO 2 > CH 4 for the four gases. Moreover, we observed that the polarizability and critical temperatures of the four gases are arranged in the same order as their adsorption capacities at both temperatures (Figure S5), indicating that these factors are crucial for gas adsorption.…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…The N 2 adsorption capacity at 273.15 K/1.0 bar is 0.61 mmol/g, and CH 4 adsorption capacities at 273.15 K/1.0 bar and 298.15 K/1.0 bar are 1.57 and 1.14 mmol/g, respectively. The adsorption data of CH 4 at 273.15 K/1.0 bar are higher than those of some materials prepared in the past two years, such as SNNU-5-Sc (1.21 mmol g −1 ), CNOP-2 (1.37 mmol g −1 ), CTP-1-NH 2 (1.50 mmol g −1 ), and MOF-2 (0.63 mmol g −1 ) . Moreover, we also gained important data about the separations of CO 2 from N 2 and CH 4 .…”
Section: Resultsmentioning
confidence: 80%
“…However, the continuous growth of carbon dioxide concentration in the atmosphere and the nuclear waste (such as radioactive iodine) produced by nuclear energy are affecting the normal life and health of human beings. It is generally believed that using a solid adsorbent to capture carbon dioxide and enrich iodine is one of the most effective strategies. So, extensive efforts have been focused on exploiting gas capture and sequestration technologies by preparing high-performance solid sorbents. …”
Section: Introductionmentioning
confidence: 99%